Antenatal Care Utilisation and Content between Low-Risk and High-Risk Pregnant Women - Yeoh, P.L.; Hornetz, K.; Dahlui, M. (Public Library of Science, 2016)
Background: The purpose of antenatal care is to monitor and improve the wellbeing of the mother and foetus. The World Health Organization recommends risk-oriented strategy that includes: (i) routine care to all women, (ii) additional care for women with moderately severe diseases and complications, (iii) specialised obstetrical and neonatal care for women with severe diseases and complications. Antenatal care is concerned with adequate care in order to be effective. Measurement for adequacy of antenatal care often applies indexes that assess initiation of care and number of visits. In addition, adequacy of care content should also be assessed. Results of studies in developed settings demonstrate that women without risk factors use antenatal services more frequently than recommended. Such over-utilisation is problematic for low-resourced settings. Moreover, studies show that a substantial proportion of high-risk women had utilisation or content of care below the recommended standard. Yet studies in developing countries have seldom included a comparison between low-risk and high-risk women. The purpose of the study was therefore to assess adequacy of care and pregnancy outcomes for the different risk groups. Methods: A retrospective study using a multistage sampling technique, at public-funded primary health care clinics was conducted. Antenatal utilisation level was assessed using a modified Adequacy of Prenatal Care Utilisation index that measures the timing for initiation of care and observed-to-expected visits ratio. Adequacy of antenatal care content assessed compliance to routine care based on the local guidelines. Results: Intensive or "adequate-plus" antenatal care utilisation as defined by the modified index was noted in over half of the low-risk women. On the other hand, there were 26% of the high-risk women without the expected intensive utilisation. Primary- or non-educated high-risk women were less likely to have a higher antenatal care utilisation level compared with tertiary educated ones (OR = 0.20, P = 0.003). Half of all women had <80% of the recommended antenatal care content. A higher proportion of high-risk than low-risk women scored <80% of the routine care content (p<0.015). The majority of the additional laboratory tests were performed on high-risk women. Provision of antenatal education showed comparatively poor compliance to guidelines, more than half of the antenatal advice topics assessed were rarely provided to the women. High-risk women were associated with a higher prevalence of adverse pregnancy outcome. Conclusions: Disproportionate utilisation of antenatal care according to risk level of pregnancy indicates the need for better scheduling of care. The risk-oriented approach often results in a tendency to focus on the risk conditions of the women. Training interventions are recommended to improve communication and to help healthcare professionals understand the priorities of the women. Further studies are required to assess the reason for disproportionate utilisation of antenatal care according to risk level and how delivery of antenatal advice can be improved, reviewing both user and provider perspectives.